Mudanças de hábitos e atitudes ocorridas em sobreviventes de infarto agudo do miocárdio após angioplastia primária - Gallo, Adriana Martins (2011)
The process of rehabilitation of any disease requires the involvement of the patient as well as his interaction with the surrounding environment. As for the acute myocardial infarction it is not different, especially when at the time of treatment the patient is made aware of some relevant factors that probably led to the acute episode. Often, by using the modern features available in current therapy, including short-term hospitalization when treatment is not invasive, such as primary angioplasty, the patient is temporarily hospitalized and barely has the notion of the seriousness of his case. The orientation regarding changes in habits and attitudes is important in that it raises awareness to initiates a secondary prevention. In face of that, came the need to seek knowledge on how patients behave after undergoing hospital and being properly advised of the changes that must be introduced in everyday life since then, always seeking the modification of risk factors for the projection of a healthy life. The aim of this study is to report the main changes in relation to the habits and attitudes of patients after their recovery from an episode of acute myocardial infarction, primary angioplasty intervention and guidance on secondary prevention. We studied 40 AMI patients who had been discharged from hospital over 12 months and had received in-hospital guidance on changes in lifestyle. We used a questionnaire developed by researchers from the literature studied. Results showed that after infarction there were changes in attitudes and habits related to diet, exercise, control of glycemic and lipid levels and smoking cessation, and also more concern and care in relation to health.